'A landmark in psychiatric progress'? The role of evidence in the rise and fall of insulin coma therapy. Issue 1 (March 2022) - Freudenthal, Robert; Moncrieff, Joanna
This paper examines the evidence behind the use and decline of insulin coma therapy as a treatment for schizophrenia and how this was viewed by the psychiatric profession. The paper demonstrates that, from the time of its introduction, there was considerable debate regarding the evidence for insulin treatment, and scepticism about its purported benefits. The randomized trials conducted in the 1950s were the result, rather than the origins, of this debate. Although insulin treatment was subsequently abandoned, it was still regarded as a historic moment in the modernization of psychiatry. Then, as now, evidence does not speak for itself, and insulin continued to be incorporated into the story of psychiatric progress even after it was shown to be ineffective.